2015
DOI: 10.3346/jkms.2015.30.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Unilateral Subacute Neuroretinitis in a Healthy Korean Male: The First Case Report in Korea

Abstract: A 52-yr-old male was referred for progressive visual loss in the left eye. The decimal best-corrected visual acuity (BCVA) was 0.01. Fundus examination revealed diffuse retinal pigment epithelial degeneration, focal yellow-white, infiltrative subretinal lesion with fuzzy border and a live nematode within the retina. Diffuse unilateral subacute neuroretinitis (DUSN) was diagnosed and the direct laser photocoagulation was performed to destroy the live nematode. During eight months after treatment, BCVA gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 19 ] Among healthy individuals, DUSN could be the cause of an unexplained unilateral vision loss. [ 10 ] As in our case, the diagnosis of DUSN is entirely clinical, while serological testing of CSD aids in the diagnosis of ocular bartonellosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[ 19 ] Among healthy individuals, DUSN could be the cause of an unexplained unilateral vision loss. [ 10 ] As in our case, the diagnosis of DUSN is entirely clinical, while serological testing of CSD aids in the diagnosis of ocular bartonellosis.…”
Section: Discussionmentioning
confidence: 70%
“…[ 9 ] Other authors have suggested that the ingestion of undercooked soil from underground plants is among the modes of larva entry. [ 10 ] It was postulated that in the intestine, worms may hatch and then travel via the blood stream to the eye. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DUSN seems to involve a local toxic effect on the retina from the worm by-products. Severe visual loss is attributed to progressive ganglion cell loss from the host's immune reaction to the toxin [1,6,7]. Early presentation is characterized by diffuse intraocular inflammation with unexplained vitritis, papillitis, and migrating crops of multiple white evanescent retinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made by Kang et al . [8] The live worm was captured on OCTA in the outer retinal slab as it was mobile. However, once the worm was immobilized post PSLP, the OCTA did not pick up the worm.…”
Section: Discussionmentioning
confidence: 99%